UPAYA PENDAMPINGAN PEMBELAJARAN DARING ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR DI BIMBA-AIUEO TANIMULYA - Ismayanti Ismayanti; Ansori Ansori; Novi Widiastuti (IKIP Siliwangi, 2023)
The research aims (1) to describe the mentoring plan carried out by parents in increasing children's learning motivation during online learning at BIMBA-AIUEO Tanimulya, (2) to find out the process of implementing the mentoring carried out by parents (3) to find out the results of the mentoring carried out by parents parents do. The research assumptions show that since the COVID-19 outbreak appeared at the end of 2019, all aspects of life cannot be carried out normally, so solutions are needed to overcome them. The theoretical basis used is the concept of out-of-school education, early childhood education theory and mentoring theory. The research method uses a qualitative-descriptive approach. Data collection techniques through (1) observation, (2) interviews, (3) literature study and (4) documentation. Data processing in the form of data checking, data selection, data classification and data tabulation. The results of the study show that mentoring is carried out to guard and strengthen children's intrinsic interest in learning from within themselves; planning for accompanying children in learning is carried out as a stimulus to reveal awareness of interest in reading and learning, parents function as a companion component that influences the creation of quality non-formal education processes and outcomes.